Emerging therapeutic strategies for precision reproductive management of repeat breeder cattle - Mohamad Agus Setiadi; Prawira Eka Wardana; Wahono Esthi Prasetyaningtiyas (ARSHI Veterinary Letters, 2026)
Repeat breeding in cattle is failure to establish pregnancy after three or more services or artificial inseminations despite cycling and no abnormalities. This causes losses from reduced conception, repeated insemination, prolonged calving interval, maintenance costs, and calf production. This review evaluates mechanisms and management, emphasizing fertilization failure, embryonic death, and uterine function. Evidence shows that it is multifactorial, involving poor oocyte competence, mistimed insemination, endocrine dysfunction, heat stress, sperm transport failure, subclinical endometritis, impaired embryo–maternal communication, endometrial gene expression, and inadequate receptivity. Management requires precise strategies tailored to the pathway.